Analysis of the gut microbiome using extracellular vesicles in the urine of patients with colorectal cancer - Hyuk Yoon; Nam-Eun Kim; Jihye Park; Cheol Min Shin; Nayoung Kim; Dong Ho Lee; Jae Yong Park; Chang Hwan Choi; Jae Gyu Kim; Young Soo Park (The Korean Journal of Internal Medicine, 2023)
Background/Aims We evaluated the gut microbiome using extracellular vesicles (EVs) in the urine of patients with colorectal cancer (CRC) to determine whether gut-microbe-derived EVs could be a potential biomarker for the diagnosis of CRC. Methods EVs were isolated from the urine of patients with CRC and healthy controls. DNA was extracted from the EVs, and the bacterial composition was analyzed using next-generation sequencing of the 16S rRNA. Results A total of 91 patients with CRC and 116 healthy controls were enrolled. We found some specific microbiomes that were more or less abundant in the CRC group than in the control group. The alpha-diversity of the gut microbiome was significantly lower in the CRC group than in the control group. A significant difference was observed in the beta-diversity between the groups. The alpha-diversity indices between patients with early- and late-stage CRC showed conflicting results; however, there was no significant difference in the beta-diversity according to the stage of CRC. There was no difference in the alpha- and beta-diversity of the gut microbiome corresponding to the location of CRC (proximal vs. distal). Conclusions A distinct gut microbiome is reflected in the urine EVs of patients with CRC compared with that in the healthy controls. Microbial signatures from EVs in urine could serve as potential biomarkers for the diagnosis of CRC.